2012
DOI: 10.1155/2012/702325
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Uterine Fibroids at Aminu Kano Teaching Hospital

Abstract: Objective. To determine the influence of age and parity on the surgical management of uterine fibroids, clinical presentation, presence of pelvic adhesions, cadre of surgeons, and postoperative complications at the Aminu Kano Teaching Hospital, Kano, Nigeria. Methods. A retrospective analysis of 105 cases of uterine fibroids that were managed between 1st January 2003 and 31st December 2007. Results. The period prevalence of uterine fibroids was 24.7% of all major gynecological operations. The mean age was 35.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
5
13
1
Order By: Relevance
“…The ratio of myomectomy to hysterectomy of about 3:1 has also been reported in the study by Garba et al [27]. Values of 41% for myomectomy [28] and 10.6% for hysterectomy [31] have also been reported. Salpingectomy was the second commonest major surgery performed at 26.4% and this is similar to the findings of 26% by Yakasai et al [29].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The ratio of myomectomy to hysterectomy of about 3:1 has also been reported in the study by Garba et al [27]. Values of 41% for myomectomy [28] and 10.6% for hysterectomy [31] have also been reported. Salpingectomy was the second commonest major surgery performed at 26.4% and this is similar to the findings of 26% by Yakasai et al [29].…”
Section: Discussionsupporting
confidence: 65%
“…These contributed 21.4% of all gynaecological operations. Common gynaecological surgeries reported in Nigerian literatures, as percentage of total procedures, include myomectomy (41.9%), salpingectomy (26.0%), manual vacuum aspiration (MVA) (21.5%), hysterectomy (10.6%) and laparoscopy (2.8%) [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in haemostatic methods and anaesthesia also play an important part in the safety and reduction in mortality and morbidity. Abdominal myomectomies are still predominantly done in the developing world with zero mortalities as was also recorded in this case 19,20,21 . This can also be due to proper case selection without conversion to hysterectomy .…”
Section: Discussionsupporting
confidence: 58%
“…17,18,23 The mean age at presentation for uterine myoma reported from various centres across this country is 35-40±6 years and least common by age 20-24. [24][25][26] Nnewi study reported that 76% and 30.1% of the women who presented with uterine myoma were nulliparous and infertile, respectively. 26 In this study, age showed a statistically significant association with comorbidity in infertility as noted between patients ≤34 years and those >35 years (p<0.05).…”
Section: Discussionmentioning
confidence: 99%